The Influence of Female Directors and Female Commissioners on Firm Performance with CSR Disclosure as an Intervening Variable - Febrianti, Citra Amanda; Ariyanto, Sanusi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of female directors and commissioners on firm performance, with CSR disclosure as an intervening variable in Basic Materials companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The population comprised all companies in the sector, with a sample of 48 companies (144 observations) selected through purposive sampling based on the availability of complete annual and sustainability reports. This study used quantitative methods and secondary data, panel data regression with E-Views testing tools in the form of classical assumption tests, t-tests, F-tests, R-Square tests, and Sobel tests to examine the mediation effect. Female directors were measured by the proportion of female directors, female commissioners by the proportion of female commissioners, firm performance by Tobin's Q, and CSR disclosure by the GRI index of 24 indicators (economic, social, and environmental). The results show that female directors do not have a significant positive effect on CSR Disclosure (H3 is rejected, p = 0.6575) and firm performance (H1 is rejected, p = 0.3896), while female commissioners have a significant positive effect on both (H2 and H4 are accepted, p = 0.0000 and p = 0.0052). CSR Disclosure does not have a significant effect on firm performance (H5 is rejected, p = 0.2672) and does not mediate the relationship between the two (H6 is rejected, the Sobel test is not significant). Adjusted R-Square for structural factor I is 0.72 and for structural factor II is 0.671. Conclusion: female commissioners can improve company performance directly, but CSR Disclosure does not play a mediating role in the Indonesian extractive sector.